An analysis of the relationship between coping strategies used and incidence of relapse in myalgic encephalomyelitis - Biccard, Anne-Marie (My University, 2016)
This dissertation studies the relationship between the use of certain coping strategies and the relapse of'illness, Eighty subjects with 1\'{yalgicEncephalomyelitis (M.E.) were followed OVera nine month period, initially completing a biographical questionnaire which showed some interesting common features, but these characteristics may be attributed to the narrow population from which the sample was drawn. The subjects then completed a battery of tests every eight weeks. These tests monitored appraisal of stressors, ways of coping and general health over the eight weeks since the previous test. Results were analysed using a Pearson's product moment correlation and a principal components factor analysis with a varimax rotation. The subjects were expected to show a positive correlat'on between certain coping techniques (such as denial, avoidance, and self- blame) and the relapse of M.B., while a zero or negative correlation between other coping techniques (such as seeking social support and problem solving when the stressor is controllable) and relapse. Neither of these hypotheses was supported by the data gathered. However, the subjects showed a remarkable consistency inthe types of'coping used, rather than adapting the mode of coping to the type of stressor experienced. It was concluded that the subjects used abnormal coping techniques and that these techniques Weresomehow related to their illness. However, the exact causal relationship between the coping techniques and the illness could not be assessed. It is possible that the subjects' poor coping mechanisms contributed to the development and exacerbation of the illness but it in also possible that the illness limited the repertoire of coping techniques available to the p"atient.
Dissertation Submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, for the degree of Master of Science. Johannesburg 1993
Keywords: Stress (Psychology); Stress (Physiology); Myalgic encephalomyelitis.